A Maqasid and Shariah Enterprises Theory-Based Performance Measurement for Zakat Institution - Ataina Hudayati; Achmad Tohirin (Center of Strategic Studies (PUSKAS) BAZNAS, 2019)
This study aims to develop a performance measurement system for zakat institutions from the perspective of maqashid al-Shariah and Islamic enterprise theory. This study embarks from previous studies focusing on the performance measurement methods applied to the zakat institutions. The understanding of maqashid al-Shariah in this paper refers to the concept formulated by Al Ghazali and Ibn Ashur. The basis of selecting so is their widely known concept in the contemporary research. This paper concludes that the performance measurement based on maqashid al-Shariah for Islamic bank can be adopted in zakat institution by making various adjustments according to the characteristics of the institution. In addition, this study also designed a performance scorecard to assess the performance of zakat institutions based on maqashid al-Sharia and Islamic enterprises theory. This scorecard method can calculate the index of zakat management of the related institution from a broader perspective.